A Hybrid Routing Protocol Based on Route Optimization Mechanism for VANET - Kaur, N; Devgan, M.S (International Journal of Computer Sciences and Engineering, 2025)
In this paper, an efficient routing algorithm along with an optimization technique named as CS (Cuckoo search) is used. CS is a metaheuristic algorithm that is used to find the best route between the source node and a destination node, on the basis of healthy function. The properties of each node on the basis of energy consumption and distance basis are found out. Therefore, the node that has efficient energy, to forward the data, along with the smaller distance is selected and hence data packets are forward to that next node. In this way, the process is continuing and the data is delivered successfully to the destination node. At last, the performance parameters such as PDR (packet delivery ratio), data overhead and delay is measured.